Locked in [large type] - Adler-Olsen, Jussi (Random House Large Print, 2024)
On the day after Christmas, head of Department Q, Detective Carl Mørck, finds himself handcuffed in a police car headed for Copenhagen's Vestre prison. After fifteen years, a violent case from his past has caught up with him. Charges of drug trafficking and murder threaten to destroy his life and career. But he is being framed. Someone has a million-dollar bounty on his head to make sure he doesn't talk, putting him in grave danger among the prison's incarcerated criminals and corrupt officers. The question that remains is, Why? Carl's colleagues at the Copenhagen Police Department instantly turn their backs on him, leaving the ever-loyal Department Q team as his only hope. In search of answers, Rose, Assad, and Gordon must disobey direct orders from way up the chain to try to unravel case. With only one another to trust and Carl's battle against the unknown mastermind's henchmen worsening by the day, they must work faster than ever before if they are to clear his name--and save his life.